PENGARUH PENGETAHUAN AKUNTANSI DAN PERCEIVED OF USEFULNESS TERHADAP PENGGUNAAN APLIKASI AKUNTANSI BERBASIS ANDROID - Ni Nyoman Yuni Rasniati; Ni Putu Ayu Kusumawati; Rai Dwi Andayani W (Hita Akuntansi dan Keuangan, 2022)
This study sought to evaluate the effects of knowledge of accounting and perceived of usefulness on the use of Android Based Accounting Applications. The location of this research in Denpasar City. This study takes a quantitative technique combining primary data using questionnaire. The sampling procedure uses the slovin formula such that 100 respondents were acquired. To meet the aims of this study, respondents are particular to SMEs in Denpasar City who utilize an android-based accounting program. Data were examined using multiple linear regression. The results showed that understanding of accounting and perceived usefulness has a substantial effect on the use of android- based accounting applications for SMEs in Denpasar City.